The wheat Seven in absentia gene is associated with increases in biomass and yield in hot climates. (5th February 2021) - Thomelin, Pauline; Bonneau, Julien; Brien, Chris; Suchecki, Radoslaw; Baumann, Ute; Kalambettu, Priyanka; Langridge, Peter; Tricker, Penny; Fleury, Delphine
Abstract : We narrowed down a genetic locus associated with improved physiology and yield components in wheat under heat stress to a gene showing sequence and expression variation. Abstract: Wheat ( Triticum aestivum L.) productivity is severely reduced by high temperatures. Breeding of heat-tolerant cultivars can be achieved by identifying genes controlling physiological and agronomical traits when high temperatures occur and using these to select superior genotypes, but no gene underlying genetic variation for heat tolerance has previously been described. We advanced the positional cloning of qYDH.3BL, a quantitative trait locus (QTL) on bread wheat chromosome 3B associated with increased yield in hot and dry climates. The delimited genomic region contained 12 putative genes and a sequence variant in the promoter region of one gene, Seven in absentia, TaSINA . This was associated with the QTL's effects on early vigour, root growth, plant biomass, and yield components in two distinct wheat populations grown under various growth conditions. Near isogenic lines carrying the positive allele at qYDH.3BL underexpressed TaSINA and had increased vigour and water use efficiency early in development, as well as increased biomass, grain number, and grain weight following heat stress. A survey of worldwide distribution indicated that the positive allele became widespread from the 1950s through the CIMMYT wheat breeding programme but, to date, has been selected only in breeding programmes in Mexico and Australia.